2020
DOI: 10.3390/genes11040461
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Phenotype–Genotype Approach Using Phenotypic Characteristics from the UAE National Diabetes Study Identifies HSD17B12 as a Candidate Gene for Obesity and Type 2 Diabetes

Abstract: The United Arab Emirates National Diabetes and Lifestyle Study (UAEDIAB) has identified obesity, hypertension, obstructive sleep apnea, and dyslipidemia as common phenotypic characteristics correlated with diabetes mellitus status. As these phenotypes are usually linked with genetic variants, we hypothesized that these phenotypes share single nucleotide polymorphism (SNP)-clusters that can be used to identify causal genes for diabetes. We explored the National Human Genome Research Institute-European Bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The integrative phenotype–genotype approach is a novel, simple, and powerful tool to identify clinically relevant potential biomarkers. We recently used this approach to identify clinically essential biomarkers in complex and heterogeneous diseases like diabetes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The integrative phenotype–genotype approach is a novel, simple, and powerful tool to identify clinically relevant potential biomarkers. We recently used this approach to identify clinically essential biomarkers in complex and heterogeneous diseases like diabetes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the obtained results suggest that regions 8q22-24, 11q23-25, and 12q13-15 are very likely to contain genes like VPS13B, APOA5, ZPR1, BUD13, and FAIM2 that control obesity-related factors in Iranian families with MetS 21,22,27,28,31,32 . A more refined analysis with high-density short tandem repeat (STR) markers in the regions of interest around the marker with the most robust evidence for linkage and association, which possibly focuses on very informative families identified in this study, is needed to pave the way to identify responsible genes.…”
Section: Discussionmentioning
confidence: 75%
“…The genome-wide analysis has recently identified genetic variants in association with waist circumference (WC) and BMI 13 , 14 . These studies found some chromosomal regions such as 8(q22.1-q24.3) containing VPS13B gene 15 22 , 11(q23.3-q25) containing APOA5, ZPR1, and BUD13 genes 23 28 , 12(q13.12-q15) containing FAIM2 gene 18 , 29 32 , and 16(q23.3-q24.3) containing MAF gene 31 33 with high LOD scores concerning BMI and WC (Table 1 ). Even some genetic variations were reported concerning MetS in the Japanese population 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The details of the study design and sampling of the UAEDIAB study are described elsewhere [15]. The study was approved by the Ethics Committee of Sharjah University and the Ministry of…”
Section: Study Design Population and Settingsmentioning
confidence: 99%
“…Four Emirati diabetic patients (age 60 ± 1, HbA1c >10.5%), fasting blood glucose values >13 mmol/L, BMI >40 and weight 120 ± 3 kgs) were subjected for targeted DNA next-generation sequencing using the S5 semi-conductor based DNA sequencer as described previously [26] [17].…”
Section: Targeted Next-generation Sequencing From T2d Emirati Patientsmentioning
confidence: 99%